PERBEDAAN HASIL BELAJAR IPA BIOLOGI MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DAN GROUP INVESTIGATION (GI) - Ester Stasya Lawalata; Alwi Smith; S Liline (Program Studi Pendidikan Biologi FKIP Unpatti, 2019)
Background: One of the causes of students' lack of understanding of a concept is teacher-centered learning and a lack of motivation from students in following the learning process. Then we need an innovative learning model that can help students in the learning process. To achieve learning objectives, teachers are required to be able to choose suitable learning models to be applied at an educational level. Method: This research was conducted from January 14 to February 14, 2020 using descriptive methods, student learning outcomes are seen through the final value that is seen based on cognitive aspects (LKS), affective and psychomotor and pre-post test scores. Measurement data were analyzed using the t test formula. Results: Based on the t test, obtained the results of tcount 1.573 and ttable 2.010, tcount <ttable, the hypothesis (H1) was rejected and (H0) was accepted. Conclusion: There is no difference in the learning outcomes of students taught using the Problem Based Learning model and Group Investigation on the material of the human digestive system in class VIII SMP Negeri 7 Ambon, but there is an increase in learning outcomes after teaching and learning using the Problem Based Learning and Group Investigation models so the results of the t-test show that tcount <ttable (1.573 <2.010).